Faktor-Faktor Yang Mempengaruhi Pendeteksian Kecurangan: Risiko Audit, Teknik-Teknik Audit Investigatif dan Whistleblowing Sistem - Desi Fitria; Cris Kuntadi; Citra Etika (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2024)
Basically, minimizing fraud can be done by detecting fraud, but reducing fraud alone is not enough. Therefore, it is necessary to detect fraud. This article reviews research on factors that influence fraud detection, namely Audit Risk, Investigative Audit Techniques, Whistleblowing Systems. The purpose of this literature review is to develop hypotheses about the influence between variables for use in further research. The results of this literature research are that the science of Internal Control, Whistleblowing Systems, and internal audit have an influence on fraud prevention. This means that the better the knowledge of Audit Risk, Investigative Whistleblowing System Audit Techniques, that one has, the better the implementation in preventing fraud.